The Effect of Personal Characteristics, Motivation and Compensation on Employee Performance with Loyalty as Intervening Variables - Siregar, Saparuddin; Nasution, Yenni Samri Juliati; Parikesit, Wuri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to analyze the influence of personal characteristics, motivation and compensation variables on performance with loyalty as an intervening variable. This research is a quantitative study with a causality research design. The sampling technique in this study was saturated sampling, which is a sampling technique using the entire population, they are lecturers and employees of Ma'had Abu Ubaidah bin Al Jarrah Medan, amounting to 43 people. The analytical method used is path analysis. The data processing process uses SPSS 22. The results show that partially, the three variables used in the study: personal characteristics, motivation and compensation have no effect on employee performance. When interpreted through loyalty variables, the two variables personal characteristics and compensation do not affect performance, but motivation variables affect performance. While loyalty has a significant effect on performance. This shows that the lecturers and employees of Ma'had Abu Ubaidah bin Al Jarrah have good loyalty and performance even though with a limited amount of Human Resources, lack of motivation and inadequate compensation. Because not only the material goals to be achieved, but the call to serve is the reason for their existence in Ma'had Abu Ubaidah bin Al Jarrah Medan.